Implementation of Dynamic Threshold Method for Human Motion Detection in Video surveillance application - Gupta, Ms. Pritee; Singh, Dr. Yashpal (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Detection of moving objects in video streams is the first relevant step of information extraction in many computer vision applications. Aside from the intrinsic usefulness of being able to segment video streams into moving and background components, detecting moving objects provides a focus of attention for recognition, classification, and activity analysis, making these later steps more efficient. This paper implemented a method to detect moving object based on background subtraction. First of all, we establish a reliable background updating model based on statistical and use a dynamic optimization threshold method to obtain a more complete moving object. The moving human bodies are accurately and reliably detected. The experiment results show that the proposed method runs quickly, accurately and fits for the real-time detection.